(untitled) (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
This article examines the psychological characteristics of developing communication culture among youth on social networks. The study analyzes the socio-psychological aspects of digital communication, including communication ethics, interpersonal interaction, emotional expression, and self-presentation in virtual environments. A content analysis method was employed to investigate the communication activities of 100 young social media users. The findings revealed that visual-oriented platforms such as Instagram and TikTok dominate youth communication, while social-oriented content and positive emotional interactions prevail in online communication. At the same time, a considerable tendency toward idealized self-presentation and the presence of negative communicative behaviors were identified. The results indicate the necessity of promoting digital communication culture, online ethical norms, empathy, and communicative responsibility among young people. The article proposes psychological and educational approaches aimed at fostering constructive communication and healthy interpersonal relationships in social networking environments.